2008
DOI: 10.1158/0008-5472.can-08-0257
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Phospho-Akt Is a Major Molecular Determinant of Bortezomib-Induced Apoptosis in Hepatocellular Carcinoma Cells

Abstract: Bortezomib, a proteasome inhibitor, has been clinically approved for the treatment of myeloma and lymphoma. Here, we report a differential effect of bortezomib on apoptosis in four hepatocellular carcinoma (HCC) cell lines and identify the major molecular event that determines sensitivity. Although bortezomib inhibited proteasome activity to a similar extent in all HCC cell lines, it showed differential effects on their viability: Huh-7 (IC 50 196 nmol/L), Sk-Hep1 (IC 50 180 nmol/L), Hep3B (IC 50 112 nmol/L), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 44 publications
7
117
0
1
Order By: Relevance
“…85,86 Recently, AKT signalling has been reported to be important for the enhanced BZ-induced apoptosis in HCC cells, through the inhibition of PI3K/ AKT pathway reports. [87][88][89] Despite the efficacy of BZ reports have also demonstrated that non-myeloma and myeloma cell lines can adapt and become resistant to to BZ-induced cell death. 90,91 The adaptation of the cells to BZ is partially due to changes, in the proteasome Figure 3.…”
Section: Atf4 and Autophagymentioning
confidence: 99%
“…85,86 Recently, AKT signalling has been reported to be important for the enhanced BZ-induced apoptosis in HCC cells, through the inhibition of PI3K/ AKT pathway reports. [87][88][89] Despite the efficacy of BZ reports have also demonstrated that non-myeloma and myeloma cell lines can adapt and become resistant to to BZ-induced cell death. 90,91 The adaptation of the cells to BZ is partially due to changes, in the proteasome Figure 3.…”
Section: Atf4 and Autophagymentioning
confidence: 99%
“…The fact that multiple cellular targets are affected by bortezomib suggests its potential advantage in enhancing antitumor activities in combination treatment with TRAIL in HCC. Indeed, in our previous study, exploring the antitumor activity of bortezomib against HCC cells (17), we showed that downregulation of p-Akt determines the sensitivity of bortezomib, and that bortezomib-induced apoptosis may not be associated with proteasome inhibition in HCC cells. Moreover, we confirmed that bortezomib sensitized HCC cells to TRAIL through inhibition of p-Akt (14).…”
Section: Introductionmentioning
confidence: 96%
“…(2) Substantial evidence from epidemiological studies indicates that HCC is strongly associated with alcohol abuse, chronic infection with hepatitis B virus (HBV) and/or hepatitis C virus (HCV), and liver cirrhosis. (3)(4)(5) More than one million people die of liver cancer worldwide every year. (6) Few patients are diagnosed in the early stage, and <20% of HCCs can be resected completely.…”
mentioning
confidence: 99%